Efficacy of Knowledge, Attitude and Practices of Households towards Municipal Solid Waste Management in Karachi - Aamir Abbas; Muhammad Imran; Yasmeen Sultana; Muhammad Zohaib Awan (UW Journal of Management Sciences, 2022)
Objective: Objectives of the present study are to assess the Efficacy of knowledge, attitude and practices of households on municipal solid waste management and to find out the environmental factors associated with health due to solid waste management which influence to health and major existing problems due to poor solid waste management system in Karachi. Methodology: In order to assess the Efficacy of knowledge, attitude and practices of households on municipal solid waste management in Karachi, present study randomly recruited 180 respondents from the five towns of two districts of Karachi. A house hold survey was conducted and 36 households were recruited from each town through stratified random sampling technique. Well-structured questionnaire was used for the data collection by using likert scale. SPSS version 22 was used for data analysis. Results: The results of the present supports that some existing practices of household, unavailability of municipal containers, unavailability of solid waste collection services, less utilization of containers and insufficient knowledge of about recycling or reuse of solid waste are responsible for adverse condition of solid waste management system in Karachi. Suggestion: Present study suggests that more consolidated strategy for solid waste management needs to be designed and implemented which streamlines the process of waste collection and disposal. Municipalities should also invest in recycling plant, so that all the recyclable material could be collected and processed at one place. Households must be educated and should be given right information of dumping the solid waste. Solid waste management laws should be implemented and citizen should be aware about the penalties.